Ismail Zain - the ambivalence approach and his shift towards The postmodern - Abdullah, Sarena (Universiti Teknologi Mara, 2012)

(untitled)
This paper will discuss a few wori(s of Ismail Zain in the larger context of ambivalent aesthetics and artistic approach that can be suggested in the reading of his earlier wort<s prior to ·Digital Collage" (1988}. Ismail Zain (1930 - 1991}, was born in Alar Setar, Kedah and educated at Ravensbourne College of Art. United Kingdom and Slade School of Art. London Unive~jty. He was the former Director of the Malaysia's National Art Gallery; Director-General of Culture, Ministry of Culture. Youth and Sports; and Director-General of tha National Film Development Corporation (FINAS}. Despite his demanding and hectic career, Ismail zaon was never out of touch from the Malaysian art world and in his life. he has produced a significant number of art wort<s that holds great importance in the Malaysian art history developmenl This first part of thos paper will discu&S Ismail Zain's works that employs the ornate and floral motives and how his works need to be contextualised and understood within the inclinations or Malay/Islamic-centred art inherent during the 1970s and 1980s and also within the incoming of postmodem art tendencies in Malaysia. Hence, I argue here that through these works he negotiated his artistic and aesthetics position within these two proclivities. The second part o f this paper will discuss briefly the artistic strategies of his more renowned work in the context of postmodern art approach.